EXPLORING HIGH-ACHIEVING EFL PRE-SERVICE TEACHERS’ UNDERSTANDING OF PEDAGOGICAL CONTENT KNOWLEDGE (PCK) THROUGH REFLECTIVE PRACTICE IN A MICROTEACHING COURSE - Tina Priyantin; Nenden Sri Lengkanawati; Ika Lestari Damayanti; Fazri Nur Yusuf (University of Kuningan, 2026)
This study aims to examine how five high-achieving EFL pre-service teachers reflect on their understanding and integration of Pedagogical Content Knowledge (PCK) during a microteaching course. Employing a qualitative method with a case study design, reflective writings before and after teaching that were posted on their digital portfolios (Blogs) were used to gather data. Thematic analysis was used to analyze data by employing deductive and inductive methods. The findings reveal that the participants demonstrated a strong understanding of language processing and production and language teaching strategies. However, while they exhibited a moderate understanding of learners’ needs, their comprehension of cognitive language learning strategies and intercultural communication remained limited. The study highlights the importance of guided reflection in helping pre-service teachers bridge theory and practice. It suggests that teacher education programs should provide explicit instruction in assessment, cognitive strategies, and intercultural competence, along with ongoing mentoring to promote deeper reflection. The study contributes valuable insights into the role of reflection in enhancing the pedagogical expertise of future EFL teachers.